Chromosome-level genome assembly and annotation of the yellow grouper, Epinephelus awoara - Weiwei Zhang; Yang Yang; Sijie Hua; Qingxin Ruan; Duo Li; Le Wang; Xi Wang; Xin Wen; Xiaochun Liu; Zining Meng (Scientific Data, 2024)
Abstract Epinephelus awoara, as known as yellow grouper, is a significant economic marine fish that has been bred artificially in China. However, the genetic structure and evolutionary history of yellow grouper remains largely unknown. Here, this work presents the high-quality chromosome-level genome assembly of yellow grouper using PacBio single molecule sequencing technique (SMRT) and High-through chromosome conformation capture (Hi-C) technologies. The 984.48 Mb chromosome-level genome of yellow grouper was assembled, with a contig N50 length of 39.77 Mb and scaffold N50 length of 41.39 Mb. Approximately 99.76% of assembled sequences were anchored into 24 pseudo-chromosomes with the assistance of Hi-C reads. Furthermore, approximately 41.17% of the genome was composed of repetitive elements. In total, 24,541 protein-coding genes were predicted, of which 22,509 (91.72%) genes were functionally annotated. The highly accurate, chromosome-level reference genome assembly and annotation are crucial to the understanding of population genetic structure, adaptive evolution and speciation of the yellow grouper.